Justice, the Digital Revolution, Society and the Individual - Zeller, Bruno, (Human Rights and Humanitarian Law E-Books Online, Collection 2025., 2025)
The effects that the digital revolution is having on the threads that make up the fabric of our society are significant. Methods of communication and the ways in which individuals interact are changing. This has led to changes to our institutions, our well known structures and our trusted hierarchies. In this book the authors investigate the instruments of change in order to grasp how justice, the construct of society and the individual can be understood. The innovations brought forward by the digital revolution are inevitable and are here to stay, indeed at times they will cause conflict. This book recognises that changes to institutions such as the law must occur for us to adapt to a new and changing environment. See Less